Production and Decomposition of Litter in Prosopis cineraria Plantation Along Canal Banks in Indian Desert - Bala, N; Kumar, Pramod; Bohra, N K; Limba, N K; Baloch, S R; Singh, B; Singh, G (Annals of Arid Zone, 2016)
Temporal dynamics of litter production and it’s decomposition in Prosopis cineraria plantation in IGNP command area has been studied. Annual litter production varied greatly with plantation age and stem density in P. cineraria being high in 17-year-old plantation (1240 kg ha-1). Lowest litter production was recorded in 4-year-old plantation (384 kg ha-1). Because of the prevailing climate in the area litter-fall is seen throughout the year. Lot of seasonal variation was observed in plantations of different age classes. Bimodal pattern of litter fall was observed where two peaks of varied intensity were recorded in summer and winter. Overall, litter production was more in winter months except Y11 plantation. Component wise, leaf litter accounted for the major part of the total litter production. It varied from 63% in 11-year-old plantations to 75% in 17-year-old plantations. Woody litter component varied from 25% to 37% in plantations of different age. Value of decomposition constant (k) was 0.7339, signifying moderate rate of decomposition. A significant positive relationship between annual total litter production and girth at breast height (GBH) as well as tree height was observed. Moderate rate of decomposition signified moderate rate of nutrient turnover in P. cineraria plantations